Pembatasan Kepemilikan dan Penguasaan Lahan Rumah Tinggal Ditengah Pembangunan Komoditas Investasi - Ruska, Afdhal -; Jaya, Febri; Tan, Winsherly (Universitas Muhammadiyah Ponorogo, 2025)
This study highlights the importance of restricting residential land ownership and control in Indonesia because land is a capital asset. This study examines the social and economic impacts of this phenomenon, focusing on the Basic Agrarian Law, and provides policy recommendations to address the conflicts and inequalities that arise. This study uses a normative legal method. The results of the study show that the authorities of the Republic of Indonesia have attempted to restrict ownership and management of land rights for residential purposes, but these efforts have not been fully effective and clearly regulated in one law. The solution to restrict this is to create legal regulations that consider legal provisions and consider philosophical, legal, and sociological bases. The limitations of this study's findings lie in the lack of elaboration of the actual implementation of efforts to restrict residential land ownership and control in Indonesia, as well as the lack of analysis of the specific obstacles faced by the authorities in implementing them. In addition, recommendations for creating new legal regulations are still general in nature and do not include concrete mechanisms or steps to integrate philosophical, legal, and sociological aspects into regulations. However, the originality of this study lies in emphasizing the importance of a holistic approach in formulating policies, which considers not only the formal legal dimension, but also social values and the philosophy of justice in dealing with land as an investment commodity. This finding provides a significant contribution to the discourse on policy reform related to land ownership, especially in the context of facing pressure from the investment market.